1996
DOI: 10.1111/j.1600-0765.1996.tb00512.x
|View full text |Cite
|
Sign up to set email alerts
|

The localization of epithelial root sheath cells during cementum formation in rat molars

Abstract: The purpose of this study was to investigate the distribution of epithelial cells and the fate of the basement membrane along the root surface of rat molars during cementogenesis, and to test the hypothesis that the Hertwig's epithelial root sheath (HERS) cells remain on the root surface if mineralization is inhibited. To demonstrate the HERS cells and basement membrane, immunohistochemistry with antibodies against keratin and laminin were used. The dentin matrix mineralization was inhibited by a single inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…In conclusion, our results are supported by a study by Alatli et al (1996), who reported that the development of cellular cementum seems to be induced when cells of the dental sac attach to the inner enamel epithelium of the HERS. Our results suggested that inner enamel epithelial cells most probably play an important role by differentiating into cementoblast when they contact mesenchymal cells of the dental sac by desmosomelike structures, and epithelial-mesenchymal interactions occur.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, our results are supported by a study by Alatli et al (1996), who reported that the development of cellular cementum seems to be induced when cells of the dental sac attach to the inner enamel epithelium of the HERS. Our results suggested that inner enamel epithelial cells most probably play an important role by differentiating into cementoblast when they contact mesenchymal cells of the dental sac by desmosomelike structures, and epithelial-mesenchymal interactions occur.…”
Section: Discussionsupporting
confidence: 90%
“…The expression of keratin by HERS in vivo has been demonstrated by several investigators (Alatli et al, 1996;Kaneko et al, 1999;Onishi et al, 1999), and as expected, HERS in vitro express keratin. Unexpected was the simultaneous expression of vimentin mRNA, although coexpression of vimentin and keratin has been reported for other epithelial cell lines maintained in culture (Zuk et al, 1989).…”
Section: Do Hers Undergo Emt?supporting
confidence: 76%
“…26 Amelogenins are primarily expressed by ameloblasts during formation of the enamel matrix of the dental crown; however, amelogenin-related proteins have also been shown to be expressed later in odontogenesis by the inner cell layer of HERS immediately prior to acellular cementum formation. 4,5 In both animal and clinical studies, the application of EMD has been shown to stimulate periodontal connective tissue attachment formation 12-14 perhaps through the reintroduction during periodontal wound healing of epithelial mesenchymal interactions that were active during development of the periodontal connective tissue attachment. 15 However, the precise mechanism of EMD stimulation of periodontal connective tissue attachment regeneration is at present unknown.…”
Section: Discussionmentioning
confidence: 98%
“…In turn, mineralization of the newly secreted dentin extracellular matrix induces the inner cell layer of HERS to synthesize and secrete an extracellular matrix on the newly formed dentin surface. 5 Proteins present in the HERS secreted matrix include proteins related to the enamel protein extracellular matrix, specifically amelogenin-related proteins. 4 After extracellular matrix secretion by HERS, the epithelial cells lose contact with the root surface and HERS dissipates; however, epithelial remnants persist in the mature periodontal ligament as cell rests of Malessez.…”
Section: Introductionmentioning
confidence: 99%